Moderating Effect of Empowerment on Servant Leadership and Church Spiritual Growth - Isaac Shaasha; Dr. Barnabé Anzuruni Msabah; Dr. Alexander Katuta Kyule (Pac University, 2024)
supported servant leadership, empowerment and spiritual leadership theories. In addition, the study bridged a number of research gaps in area of servant leadership, empowerment and church spiritual growth indicated in the statement of the problem. The most noticeable gap is the contextual gap where many studies on church growth only delved on numerical growth and leaving out spiritual growth of which this study addressed. The study recommended that the church should put more emphasis on active participation of church members in decision making processes especially on provision of suggestion boxes within the church premises for this triggers church spiritual growth. The church was recommended to adopt servant leadership style and endeavor to empower the membership so as to realize church spiritual growth.